Pelayanan Administrasi Masyarakat Berbasis Platform Carrd.Co Di Desa Randugunting - Suni, Alfa Faridh; Saputra, Hermawan Rizqi; Hermayati, Tiara Widya (Universitas Negeri Semarang, 2025)
Access to technology which continues to develop very rapidly means that the government, especially at the village government level, must start developing a service system that is oriented towards the use of digital technology. The purpose of this community service is technology-based village service education that can make it easier for the community to access village documents. The community service method applied is socialization and training targeting the village community and village officials. The results of the community service show that the community and village officials can use carrd.co as a medium for providing information regarding the requirements for making various civil population administration documents, such as civil population letters such as birth certificates, death certificates, KK (Family Cards), and so on. In addition, by using carrd.co which is integrated with the Randugunting Village Instagram, the community can also easily access the village government structure, village activities, village administration services, and others. With the comprehensive and sustainable use of digital technology, it is hoped that it can bring the village towards a digital and modern direction.